Mutations in Host Cell Factor 1 Separate Its Role in Cell Proliferation from Recruitment of VP16 and LZIP - Mahajan, Shahana S. (American Society for Microbiology, 2000)
Host cell factor 1 (HCF-1) is a nuclear protein required for progression through G(1) phase of the cell cycle and, via its association with VP16, transcriptional activation of the herpes simplex virus immediate-early genes. Both functions require a six-bladed β-propeller domain encoded by residues 1 to 380 of HCF-1 as well as an additional amino-terminal region. The β-propeller domain is well conserved in HCF homologues, consistent with a critical cellular function. To date, the only known cellular target of the β-propeller is a bZIP transcription factor known as LZIP or Luman. Whether the interaction between HCF-1 and LZIP is required for cell proliferation remains to be determined. In this study, we used directed mutations to show that all six blades of the HCF-1 β-propeller contribute to VP16-induced complex assembly, association with LZIP, and cell cycle progression. Although LZIP and VP16 share a common tetrapeptide HCF-binding motif, our results reveal profound differences in their interaction with HCF-1. Importantly, with several of the mutants we observe a poor correlation between the ability to associate with LZIP and promote cell proliferation in the context of the full HCF-1 amino terminus, arguing that the HCF-1 β-propeller domain must target other cellular transcription factors in order to contribute to G(1) progression.